2019
DOI: 10.1039/c8gc03461c
|View full text |Cite
|
Sign up to set email alerts
|

Competing reactions limit levoglucosan yield during fast pyrolysis of cellulose

Abstract: Efforts to understand the reaction mechanisms of cellulose pyrolysis have been stymied by short reaction times and difficulties in probing the condensed phase of cellulose intermediate products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 52 publications
2
44
0
Order By: Relevance
“…This is in line with other studies that have found no evidence for hydrolysis to be a primary pathway. 25,26 These differences between theory and experiment suggest a need for re-examining the intramolecular bondmaking and bond-breaking events that influence glycosidic bond activation with a special emphasis on explaining the peculiar similarity between α and β-isomers.…”
mentioning
confidence: 99%
“…This is in line with other studies that have found no evidence for hydrolysis to be a primary pathway. 25,26 These differences between theory and experiment suggest a need for re-examining the intramolecular bondmaking and bond-breaking events that influence glycosidic bond activation with a special emphasis on explaining the peculiar similarity between α and β-isomers.…”
mentioning
confidence: 99%
“…A cellulose chain with DP of 2048 was chosen as the starting point, which is a reasonably close to the DP value of 1871 for cellulose reported by Lindstrom et al [18].…”
Section: Methodsmentioning
confidence: 63%
“…2% LG in quartz tube reactor at a temperature of 530 o C. Increasing the residence time reduced this yield to 53.1%, whilst increasing the reaction temperature to 630 o C at the shorter residence time reduced the yield to 51.1%. Patwardhan et al [17] achieved yields of 58.8% at 500 o C using a single shot micropyrolyser whilst Lindstrom et al [18] reported LG yields of 54.4% using a CPD-Quench micropyrolyser at the same temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of K in biomass ash has a catalytic effect on pyrolysis, favoring the yield of phenolics in bio-oil 20 . The alkali and alkaline earth metals naturally present in biomass ash serve as strong ring-fragmentation catalysts, likely due to ion–dipole forces, yielding to light acid oxygenated compounds and a chemical unstable bio-oil 21 .…”
Section: Resultsmentioning
confidence: 99%